Palm-sized quadrotor source localization using modified bio-inspired algorithm in obstacle region - Rausyan Fikri, Muhamad; Wibowo Djamari, Djati (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This paper uses a palm-sized quadrotor to demonstrate the gas source localization (GSL) in obstacle regions. The chemical substance performs a dilute dispersion in the air, and it is challenging to locate the source position. The difficulty level of the GSL increases if the location is in the obstacle region. To estimate the gas source position, it indeed uses high computational cost systems. However, it leads to a new problem: a palm-sized quadrotor has a limited size and payload capacity. In this paper, a search based on the silkworm moth is employed. The algorithm works straightforwardly as the detection gas triggers its motion. A repulsion function is integrated into a searching method to compensate the algorithm for working in single surface obstacle regions. The validation data and the palm-sized quadrotor design are provided to convince the search effectiveness performance.